Analisis Persepsi Guru Pendidikan Jasmani Terhadap Penggunaan Teknologi Informasi Dan Komunikasi - Rinaning Tyas Kusuma Dewi; Rizki Apriliyanto; Topo Yono (Corner: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
The purpose of this study was to determine the perceptions of physical education teachers in Kaliwates District, Jember Regency on the use of information and communication technology in learning. The rise of technology has changed students' behavior and attitudes, and has changed the way they learn and communicate inside and outside the classroom. Today's education has evolved as a result of the extensive use of digital technology. Digitalization now mandates that all aspects of human society use technology, including education. To combine technology and learning, today's teachers must possess technological pedagogical content expertise. health and exercise Physical education is learning that incorporates physical movement activities in order to maximize students' potential in terms of knowledge (cognition), behavioral attitudes (affective) through instilling positive values in learning, as well as psychomotor (active movement) that has implications in life. As a result, the existence of physical education learning can aid in the development of individual abilities both motorically, emotionally, and intellectually. The results of this survey, which used a descriptive quantitative methodology, show that 38% of physical education teachers in the Kaliwates District believe their students have "enough mastery" of the use of information and communication technology in their lessons. The results demonstrate that some teachers have a limited awareness of how information and communication technologies are used in education. This will help physical education instructors better comprehend and advance students' use of information and communication technologies.